Kinetically Controlled Polymorphic Superstructures of Pyrene‐Based Asymmetric Liquid Crystal Dendron: Relationship Between Hierarchical Superstructures and Photophysical Properties. Issue 36 (8th June 2018) - Park, Minwook; Kang, Dong‐Gue; Choi, Yu‐Jin; Yoon, Won‐Jin; Koo, Jahyeon; Park, Seo‐Hee; Ahn, Seokhoon; Jeong, Kwang‐Un
Abstract: To understand the relationship between kinetically controlled hierarchical superstructures and photophysical properties, pyrene‐based asymmetric liquid crystal (LC) dendrons (abbreviated as PD) were newly synthesized by covalently attaching a pyrene moiety (P) at a biphenyl‐based LC dendritic group (D). The phase transition behavior of PD has been systematically studied with a combined technique of thermal analysis, microscopy, spectroscopy, and scattering analysis. PD formed two different crystalline structures depending on the cooling rate: a stable crystalline phase (Ks, slow cooling) and a metastable crystalline phase (Kms, quenching). The kinetically controlled molecular packing structures of PD depend on the competition and cooperation of intermolecular physical interactions with nanophase separation. Upon slow cooling, the PD dimer formed by intermoelcular H‐bonding constructed a layered hierarchical structure with the help of nanophase separation. Owing to the strong π–π stacking (J‐aggregation) with weak H‐bondings, the PD dimer in the layer was slightly tilted to give a monoclinic layered structure with a periodic layer d ‐spacing of 6.6 nm. In contrast, the metastable Kms phase formed by the quenching process showed a significant tilt of the PD dimer in the layer ( d ‐spacing=4.4 nm) due to the weak π–π stacking (H‐aggregation) and the strong H‐bondings. Abstract : Monotropic transitions : Pyrene‐based asymmetric liquid crystal dendron was newly synthesized to understand the relationship between the kinetically controlled hierarchical superstructure and its properties (see figure).